Sustaining the Local: An Alternative Approach to Sustainable Design. (March 2015) - Peters, Terri
Abstract : By implication, the developmentof experimental architecture that is responsive to the local context can have sustainable benefits for the natural environment and adjacent community. Here, architect and writerTerri Peters, who has a PhD in sustainable building transformation, picks up the gauntlet and asks how the notion of localness might be able to advance sustainable design. Focusing on a qualitative rather than quantitative interpretation of sustainability, she describes projects by New York‐based studio The Living, the Chinese architect Li Xiaodong and Toronto architects Superkül, highlighting the importance of ecology, social sustainability and context‐specific design in the treatment of their work.